Navigating through an "ecological desert and a sociological hell": A cyber-systemic governance approach for the Anthropocene. Issue 6 (1st June 2015) - Ison, Ray; Schlindwein, Sandro Luis
Abstract : Purpose: – The governance of the relationship between humans and the biophysical world has been based on a paradigm characterized by dualistic thinking and scientism. This has led to the Anthropocene. The purpose of this paper is to reframe human-biosphere governance in terms of "cyber-systemics", a neologism that is useful, the authors argue, not only for breaking out of this dualistic paradigm in human-environmental governance but also of the dualism associated with the use of systems and cybernetics. Design/methodology/approach: – In this paper the authors draw on their own research praxis to exemplify how the intellectual lineages of cybernetics and systems have been mutually influencing their doings, and how new forms of governance practices that explore different framing choices might contribute to building innovative governance approaches attuned to the problematique of the Anthropocene, for instance through institutional designs for cyber-systemic governance. Findings: – The growing popularity of the Anthropocene as a particular framing for the circumstances, if it is to transformative and thus relevant demands informed critique if it is to help change the trajectory of human-life on earth. The authors offer arguments and a rationale for adopting a cyber-systemic perspective as a means to avoid the dangers in pursuing the current trajectory of our relationship with the biophysical world as, for example, climate change. The essay frames an invitation for a systemic inquiry into forms of governance more suited to the contemporary circumstances of humans in their relationships with the biophysical world. Research limitations/implications: – The research essay challenges many taken-for-granted epistemological assumptions within the cybernetics and systems intellectual communities. A case for radical change is mounted; the means to effect this change, other than through changes in discourse remain unclear though it is apparent that changes to praxis and institutional forms and arrangements will be central. Practical implications: – Cyber-systemic capabilities need to be developed; this requires investment and new institutions that are conducive to cyber-systemic understandings and praxis. Originality/value: – Understanding the global environmental crisis as an emergent outcome of current commitments to dualistic governance choices demands a reframing of much of what humans have done, re-investment in cyber-systemics offers a moral and practical response.